Father-Son Conflict from Mythological and Archetypal Perspectives - Solhdoost, Mohsen (2010)
The purpose of this study is to examine the cross-cultural conception of father-son relationship / conflict through analysis of heroic features, unconscious motives, and conscious actions of two fathers and two sons as the heroes of the stories with different mindsets in the main chapter of Shahnameh, “Rostam and Sohrab,” and Oedipus Rex. This study is to further analyze the distinguishing characters of archetypes as primordial images which, despite being prototypal, may have different representations in different myths of different nations. Further on, this study aims to compare and contrast both similarities and differences in demonstration of same archetypes transcending time and place in two distant cultural settings. of Frazer and Frye. An interdisciplinary approach has been actually applied as the conceptual theory to conduct this study. As the result of this study, we see how the same archetypes are presented differently in two different socio-cultural settings. As discussed, it is shown how a hero is respected in the Persian and Greek society. Highlighting the father-son relationship in the two cultures, we see how the two societies react differently to the father-son conflict. And finally we realize that the same archetypes are likely to be demonstrated differently in different places and time-settings. The methodology used to undertake this research consists of Freud’s theory of psychoanalysis, Jung’s theory of archetypes, as well as the anthropological standpoints